Characterization of the secretome of human tooth germ stem cells (hTGSCs) reveals neuro-protection by fine-tuning micro-environment - YARAT, AYŞEN (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2013)
Bone-marrow-derived mesenchymal stem cells (MSCs) demonstrate neuro-protective effects in several disease models. By producing growth-factors, cytokines and chemokines, they promote survival of neurons in damaged brain areas. Alternative MSC sources, such as human tooth germ stem cells (hTGSCs), have been investigated for their neuro-protective properties. They ameliorate effects of neuro-toxic agents by paracrine mechanisms, however these secreted bin-active molecules are not yet characterized. Therefore, the current study aimed to provide a detailed analysis of the secretome of hTGSCs. Brain cells were exposed to various toxic materials, including Alzheimer's beta-amyloid peptide (beta-AP) and 6-hydroxy-dopamine (6-OHDA). When co-cultured with hTGSCs, the activity of a number of anti-oxidant enzymes (catalase, glutathione-s-transferase, glutathione-peroxidase, superoxide-dismutase) was increased and neuronal death/apoptosis was subsequently reduced. The composition of the secreted bio-active materials is influenced by various pre-existing factors such as oxygen and glucose deprivation and the age of cells (passage number). This report reveals for the first time that the neuro-protective secretome of hTGSCs and the micro-environment of cells have a mutual and dynamic impact on one another. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Bio-active molecules; Cytokine; Human tooth germ stem cells (hTGSCs); Neuro-protection; Secretome; Toxicity; MESENCHYMAL STROMAL CELLS; GROWTH-FACTOR; BONE-MARROW; IN-VITRO; DIFFERENTIATION; TRANSPLANTATION; MIGRATION; SCLEROSIS; INJURY; TISSUE